A Numerical Study of Ground Displacement and Stress Conditions of Small and Medium Circular Diaphragm Wall during Excavation - Zun-Qun Xiao; Jian Lin; Dong-Sang Tang (Advances in Civil Engineering)
In the present study, a dimensional total-stress elasto-plastic FEM analysis was conducted, which was based on the Mohr-Coulomb constitutive model. The model was combined with a practical engineering case in order to investigate ground displacements and stress conditions during the installations of a medium-sized and a small-sized circular diaphragm wall, as well as the subsequent soil excavations within the walls. The distribution characteristics of the lateral radial displacements and stress conditions in the ground following the wall installations and excavations within the walls were investigated. Also, two different excavation methods, as well as three different soil depths for the walls, were considered. The distributions of the internal forces along the depth directions of the radial sections of the walls were also analyzed in this study. The analysis results showed that the slotting order had made the model nonaxisymmetric, which had further influenced the distribution characteristics of radial stress and displacements. It was found that the distributions of the horizontal radial displacements, along with the stress levels of the soil behind the walls, were only minimally affected by the excavations of the soil in the shaft. The internal force distribution of the wall radial section caused by the direct excavation method and the reverse excavation method is very small, that is, the wall bending moment generated by the reverse excavation process is larger, and the most obvious near the rock-socketed depth. The distribution pattern of the bending moment depth corresponding to different excavation construction methods is similar. Furthermore, the soil penetration depths of the walls were determined to have had little influence on the internal force distributions of the radial sections of the walls above the foundation pit. However, there was a greater influence observed on the internal force distributions of the radial sections of the walls below the foundation pit.